2020
DOI: 10.3389/fped.2020.00302
|View full text |Cite
|
Sign up to set email alerts
|

Management of Community-Acquired Pneumonia in Pediatrics: Adherence to Clinical Guidelines

Abstract: Objectives: To evaluate adherence to guidelines for inpatient care of pediatric patients with community-acquired pneumonia (CAP). Background: Pediatric CAP is one of the most common acute infections requiring hospital admission. Discrepancies between recommended care and effective management are reported, raising the necessity to evaluate our local clinical practices. Patients and Methods: Retrospective data review of all children hospitalized for CAP at our institution was conducted between 2014 and 2017. Adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
3
14
1
Order By: Relevance
“…Patients' mean age was 1.79 years and it ranged from 2 month to 7 years, and weight ranged from 3 to 21 Kg with a mean of 9.61 Kg. These findings were in agreement with the study of Hatem et al (8) , and Tannous et al (9) who showed that 60.4% of patients were males and 39.5% were females. On the contrary, Mathew et al (10) found that there were no major differences in gender.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Patients' mean age was 1.79 years and it ranged from 2 month to 7 years, and weight ranged from 3 to 21 Kg with a mean of 9.61 Kg. These findings were in agreement with the study of Hatem et al (8) , and Tannous et al (9) who showed that 60.4% of patients were males and 39.5% were females. On the contrary, Mathew et al (10) found that there were no major differences in gender.…”
Section: Discussionsupporting
confidence: 94%
“…As regard blood culture, 66.7% were -ve, 11.1% were contaminated and 22.2% were +ve (most frequent organism was Staph 13%). The study of Hatem et al (9) revealed that most of the identified microbes were isolated from culture of respiratory specimens and blood. They found that S. aureus 35.4% was the most common pathogen detected in sputum regardless the age group, candida was 12.5%, Klebsiella was 8.33%, and Pseudomonus was 4.16%.…”
Section: Discussionmentioning
confidence: 99%
“… 36 In terms of disease severity, the group of cases in our study does not seem to differ from children included in other studies on hospitalisations for ARI (including, but not exclusively, CAP) in comparable settings. 37 Although overall case severity showed a good representation of the intended group, it is nonetheless possible that convenience sampling biased associations between detected pathogens and hospitalisation in either direction.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, it reduces antimicrobial resistance, possible adverse effects and costs, while, on the other hand, it improves adherence to treatment [ 6 – 9 ]. However, despite current evidence avoiding unnecessarily prolonged treatments remains an arduous task, likely due to a false sense of security provided by longer-term treatments [ 21 ]. In fact, a retrospective study carried out in the United States in patients admitted for CAP, observed that the average duration of antibiotic treatment exceeded the recommended time by 74 and 71% for patients aged 18–64 years and ≥ 65 years, respectively [ 22 ].…”
Section: Discussionmentioning
confidence: 99%